Clinical and genetic characterization of a Chanarin Dorfman Syndrome patient born to diseased parents - Durdu, Murat (BMC Med Genet, 2018)
BACKGROUND: Chanarin Dorfman Syndrome (CDS) is a rare autosomal recessive disorder characterized by ichthyosiform non-bullous erythroderma and variable involvement of the liver and the neuromuscular system. In CDS patients, the accumulation of neutral lipids inside cytoplasmic lipid droplets has been demonstrated in different tissues. To date, ninety families with this disease have been described worldwide; most of them are from Mediterranean countries. CASE PRESENTATION: In this report, we describe a consanguineous Turkish family with typical features of CDS. The parents are first cousins and are both diseased. At the age of eight, their child presented CDS with non-bullous congenital ichthyosiform erythroderma, hepatosteatosis, hepatomegaly and ectropion. Electromyographic examination is compatible with myopathy. A five-year-old cousin of the child is also affected by CDS. She was born to non-affected consanguineous parents. Mutation analysis of the ABHD5 gene revealed the previously reported mutation, N209X, which is the most frequent in Turkish patients. Lipid vacuoles, also known as Jordan’s anomaly, are detectable in their leucocytes. CONCLUSIONS: To the best of our knowledge, this is the first report of a CDS family in which both parents and their child are affected by CDS. To date, the child does not present a more severe clinical phenotype compared with those of his relatives or other CDS patients of the same age. These findings suggest that high levels of triacylglycerol accumulation, that may be supposed to be present in high amount inside the ooplasm, did not affect embryo development and foetal growth. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12881-018-0610-0) contains supplementary material, which is available to authorized users.